Integrating deep learning algorithms to overcome challenges in big data analytics - Sujatha, R.; Aarthy, S. L.; Vettriselvan, R. (Green engineering and technology: Concepts and applications, 2022)
Data science revolves around two giants: Big Data analytics and Deep Learning. It is becoming challenging to handle and retrieve useful information due to how fast data is expanding. This book presents the technologies and tools to simplify and streamline the formation of Big Data as well as Deep Learning systems. This book discusses how Big Data and Deep Learning hold the potential to significantly increase data understanding and decision-making. It also covers numerous applications in healthcare, education, communication, media, and entertainment. Integrating Deep Learning Algorithms to Overcome Challenges in Big Data Analytics offers innovative platforms for integrating Big Data and Deep Learning and presents issues related to adequate data storage, semantic indexing, data tagging, and fast information retrieval. FEATURESProvides insight into the skill set that leverages one’s strength to act as a good data analystDiscusses how Big Data and Deep Learning hold the potential to significantly increase data understanding and help in decision-makingCovers numerous potential applications in healthcare, education, communication, media, and entertainmentOffers innovative platforms for integrating Big Data and Deep LearningPresents issues related to adequate data storage, semantic indexing, data tagging, and fast information retrieval from Big DataThis book is aimed at industry professionals, academics, research scholars, system modelers, and simulation experts